(untitled) (Revista Científica Integrada, 2023)
Objective: To analyze the reliability characteristics in the use of lead-free alloys used in the electrical union, by soft soldering, of electronic circuits. Methods: This is a narrative review, carried out in 2023, focused on the mechanical simulation of the performance of these alloys in Ball Grid Array (BGA) type electronic components joints, performed by soft soldering, including studies from the last five years, so that to describe the particularities of the mechanical-metallurgical phenomena present in these alloys, especially regarding thermal fatigue, the main degradative phenomenon associated with their failures. Results: The results indicate that SAC joints have different degrees of effectiveness, depending on the distribution and position of the spheres (balls). Furthermore, certain conditions linked to the proximity to the eutectic point of the alloys and the formation of intermetallic compounds were relevant. Conclusions: The form of analysis addressed can be advantageous to evaluate different geometries (architectures) of BGA joints, but it needs further complements to cover the effects of the mechanisms of microstructural alteration of the studied alloys.